Upaya meningkatkan kemampuan kognitif siswa kelas xi SMAN 4 kota serang melalui penerapan model pembelajaran kooperatif tipe jigsaw - Iing Dwi Lestari; Bambang Ekanara; Dian Eka Purwaningsih (Indonesian Journal of Educational Development, 2021)
This study aims to determine the increase in students' cognitive abilities through jigsaw learning. This research is a classroom action research using two cycles. The subjects in this study were students of SMA Negeri 4 Kota Serang class XI MIPA in the odd semester of the 2018/2019 academic year. The object of research is students' cognitive abilities. Data on students' cognitive abilities were collected using a cognitive ability test instrument on the concept of plant tissue structure. Data were analyzed descriptively qualitatively. The results showed an increase in students' cognitive abilities before and after the action research. This action research is declared successful if it has achieved a cognitive average score at the minimum that is equivalent to the KKM value = 70. The results showed that the average value of students' cognitive abilities before the research action was 36.32, then increased to 48.23 after the first cycle, and increased again to 72.86 at the final session (cycle II). The conclusion of this study is that the application of the jigsaw learning model in learning is able to improve students' cognitive abilities on the concept of plant tissue structure. Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan kognitif siswa melalui pembelajaran jigsaw. Penelitian ini merupakan penelitian tindakan kelas dengan menggunakan yang dilakukan dalam dua siklus. Subjek dalam penelitian ini adalah siswa SMA Negeri 4 Kota Serang kelas XI MIPA semester ganjil tahun pelajaran 2018/2019. Objek penelitian adalah kemampuan kognitif siswa. Data kemampuan kognitif siswa dikumpulkan menggunakan instrumen tes kemampuan kognitif pada konsep struktur jaringan tumbuhan. Data dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan adanya peningkatan kemampuan kognitif siswa sebelum dan sesudah penelitian tindakan.  Penelitian tindakan ini dinyatakan berhasil bila telah mencapai nilai rata-rata kognitif secara klasikal minimal setara dengan nilai KKM=70. Hasil penelitian menunjukkan bahwa nilai rata-rata kemampuan kognitif siswa sebelum tindakan penelitian sebesar 36,32, kemudian meningkat menjadi 48,23 setelah siklus I, dan meningkat lagi menjadi 72,86 pada sesi akhir (siklus II). Kesimpulan dari penelitian ini adalah penerapan model pembelajaran jigsaw dalam pembelajaran mampu meningkatkan kemampuan kognitif siswa pada konsep struktur jaringan tumbuhan.